Increased application of the 'six right' principle in the administration of drugs by nurses among the inpatient room through the supervision of the reflective model - Nuryani, Eni; Dwiantoro, Lucky; Nurmalia, Devi (Universitas Aisyah Pringsewu, 2020)
The Six Rights Of Medication Administration is a procedure and legality for nurses in the hospital. The results of the previous study indicate that nurses' compliance in applying Six right Of Medication Administration is still low. Reflective model supervision is needed to improve the correct application of six right on medication administration in a very interactive and active way of learning. This study was aimed to evaluate the influence of the reflective supervision model on the correct application of the six rights of medication administration by nurses. The study was conducted with a Quasi-experimental method pre-posttest control group design, intervention supervision of the reflective model was given to the intervention group for 2 weeks. The population of this study is all nurses in the inpatient room. The number of samples was 78 nurses, consisting of 39 nurses as an intervention group and 39 nurses as a control group. Sampling was done by purposive sampling technique (non-probability sampling). Statistical analysis using Wilcoxon and Mann-Whitney. The results showed that there were differences in the application accuracy of the six rights principles medication by nurses after being given an intervention (p = 0.001 less than 0.05). The Spearman Correlation test results that the Rho value = 0.657 can be concluded that there is a strongly significant influence of the reflective supervision model on the application accuracy of the six rights principles medication by nurses. It is recommended for the headroom to provide a reflective supervision model routinely to maintain and improve the application accuracy of the six rights principles medication by nurses. Peningkatan ketepatan penerapan prinsip enam benar obat oleh perawat di ruang rawat inap melalui supervisi model reflektifAbstrak: Prinsip enam benar obat merupakan prosedur dan legalitas bagi perawat di rumah sakit. Hasil riset sebelumnya perawat dalam menerapkan prinsip enam benar obat masih rendah. Supervisi model reflektif diperlukan untuk meningkatkan ketepatan penerapan prinsip enam benar obat dengan cara yang sangat interaktif dan aktif belajar. Tujuan penelitian ini adalah untuk mengetahui pengaruh supervisi model reflektif terhadap ketepatan penerapan prinsip enam benar obat oleh perawat. Penelitian dilakukan dengan metode Quasy experimental pre-post test control group design, intervensi supervisi model reflektif diberikan kepada kelompok intervensi selama 2 minggu. Populasi adalah perawat di ruang rawat inap. Jumlah sampel adalah 78 perawat terdiri atas kelompok intervensi 39 perawat dan kelompok kontrol 39 perawat. Pengambilan sampel dilakukan dengan teknik purposive sampling (non probability sampling). Analisa statistik menggunakan Wilcoxon dan Mann-Whitney. Hasil penelitian menunjukkan bahwa terdapat perbedaan ketepatan penerapan prinsip enam benar obat oleh perawat sesudah diberikan intervensi (p = 0,000 kurang dari 0,05). Hasil uji Korelasi Spearman bahwa nilai Rho = 0,657 dapat disimpulkan terdapat pengaruh yang signifikan kuat supervisi model reflektif terhadap ketepatan penerapan prinsip enam benar obat oleh perawat. Disarankan bagi kepala ruang untuk memberikan supervisi model reflektif secara rutin untuk mempertahankan dan meningkatkan ketepatan penerapan prinsip enam benar obat oleh perawat.